Highly Efficient On-Site Detection of Neutron Sources With the INT Measurement Car DeGeN - Berky, Wolfram; Glabian, Jeannette; Koble, Theo; Lehmacher, Thomas; Risse, Monika (IEEE sensors letters, 2018)
Counteracting the potential misuse of nuclear and radioactive material has been a subject of tremendous importance for quite a while, and the detection of such material is a key figure to counteracting measures in that respect. Especially regarding nuclear material, detecting gamma and neutron radiation simultaneously on-site with high efficiency provides a good chance of retrieving such material during transport after it was removed from nuclear facilities, either as a malicious act or simply by chance. The measurement car DeGeN (detection of gammas including neutrons) of Fraunhofer Institute for Technological Trend Analysis (INT's) is equipped with highly sensitive 3He neutron detectors and 12 l-plastic detectors for gammas. After a reconfiguration of the measurement system, including new gamma detectors, the INT was given the opportunity to verify the system's detection limits at the premises of Bundeswehr Research Institute for Protective Technologies and CBRN Protection (WIS), Munster, Germany. Two different neutron sources were used for the experimental determination of the detection limits concerning neutrons. The results were then compared with theoretical detection limits that had been calculated previously. The results proved to be in good agreement overall.